Hiperrealitas dan Krisis Identitas Manusia Post-Modern: Hyperreality and Identity Crisis of Postmodern Society - Rabiatul Adawiyah; Indra, Indra (Center of Islamic and Occidental Studies, 2023)
This article aims to review the phenomenon of hyperreality experienced by postmodern society and how Islam responds to it. Caused by the development of information technology, especially internet or cyberspace, hyperreality shapes behaviour patterns in people's lives. They are unable to distinguish between reality and fantasy. This phenomenon then creates an identity crisis. In Islam, it needs serious attention because it falls into the category of nifāq. Using descriptive-analytical methods, this article reviews the problems of Western society in interpreting reality and self, freedom and human rights, to be answered with Islamic teachings about it. The article finds that the phenomenon of hyperreality of Western society also affects Muslims today. Unlike Western societies that uphold value freedom and relativism, Islam has taught its followers to be servants and caliphs on earth who have a mandate to do good and spread goodness; to do what is right and to forsake evil. This is the identity of the Muslims. They must not deceive in the name of rights and freedoms to present a false reality. Since rights and freedoms are closely related to goodness.